2021
DOI: 10.1021/acsabm.1c01039
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Synthesis of a Covalent Organic Framework and Its Application in Multifunctional Tumor Therapy

Abstract: For decades, covalent organic frameworks (COFs) have attracted wide biomedical interest due to their unique properties including ease of synthesis, porosity, and adjustable biocompatibility. Versatile COFs can easily encapsulate various therapeutic drugs due to their extremely high payload and porosity. COFs with abundant functional groups can be surface-modified to achieve active targeting and enhance biocompatibility. In this paper, the latest developments of COFs in the biomedical field are summarized. Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 144 publications
0
22
0
Order By: Relevance
“…804 COFs are latecomers, since they joined the nanooncology candidate library in the 2010s, but they have shown some advantages. 117,714,805,806 COFs are highly diverse in terms of structure, particle size, charge, hydrophilicity, surface chemistry and other physicochemical properties, 807 and thus, their biological interactions are not only manifold but also controllable, with great scope for customization. 808 As nanoplatforms, COFs easily integrate multiple diagnostic and therapeutic strategies to achieve nanotheranostics.…”
Section: Biomedicinementioning
confidence: 99%
“…804 COFs are latecomers, since they joined the nanooncology candidate library in the 2010s, but they have shown some advantages. 117,714,805,806 COFs are highly diverse in terms of structure, particle size, charge, hydrophilicity, surface chemistry and other physicochemical properties, 807 and thus, their biological interactions are not only manifold but also controllable, with great scope for customization. 808 As nanoplatforms, COFs easily integrate multiple diagnostic and therapeutic strategies to achieve nanotheranostics.…”
Section: Biomedicinementioning
confidence: 99%
“…COFs may sustain steady structure throughout the process. As a result, COFs are employed as transporters in drug chemotherapy to distribute medications to target [ 115 ]. Zhao’s group prepared PI-3-COF and PI-2-COF (imine 2D COFs) in 2017 and investigated their drug-loading actions [ 94 ].…”
Section: Applicationsmentioning
confidence: 99%
“…MTT assays and fluorescence microscopy were used to investigate cell migration and absorption, and the results revealed that the system had effective cancer cell targeting. The effective localization of cancer cells in breasts has considerable capability for the delivery of drugs despite the minimal drug loading [ 115 ].…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key reason for these issues is that MW hyperthermia is not sufficiently focused; therefore, the temperature attained in a specific area may be insufficient for eradicating a tumor. The size, location, and complex biology of tumors make it difficult to effectively control the tumor temperature. , To solve this problem, researchers have developed a series of MW sensitizers, among which metal–organic frameworks (MOFs) have shown ultrahigh MW-heat conversion efficiencies, improving the outcomes of MW treatment. ,, The common preparation methods of MOFs are often time-consuming and low in efficiency; , thus, researchers have been searching for fast and efficient MOF synthesis methods and exploring new MOFs for clinical tumor treatment. Spray pyrolysis is a green rapid synthesis method with broad application prospects, which may potentially be the sought for fast and efficient MOF synthesis method . For example, Ceren et al synthesized spherical porous ZrMOF by continuous flow spray drying. , However, MOF materials prepared by conventional spray methods are often micrometer-sized, and the excessively large particle size limits their application in the biological field.…”
Section: Introductionmentioning
confidence: 99%